A influência do afastamento por acidente de trabalho sobre a ocorrência de transtornos psíquicos e somáticos - Borsonello, Elizabethe Cristina [UNESP]; Santos, Leila Cristina Dos [UNESP]; Schmidt, Maria Luiza Gava [UNESP]; Andrade, Telma Gonçalves Carneiro Spera De [UNESP] (Conselho Federal de Psicologia, 2002)
The present study has the goal of verifing the association between the removal by work accident and the occurrence of anxiety and depression, checking if this first factor had influence in the appearance of somatic disturbances and/or disturbances in the social relationships of the individuals. In all the cases studied, it was noted that there was a significative increase in the symptoms after the removal and that the return to work was not possible because of the persistence of the pathology and the development of other manifestations. Thus, the removal was considered a stressor stimulus, since it has caused psychological disturbances and also occasioned organic modifications.

O presente estudo teve como objetivo verificar a associação entre o afastamento por acidente de trabalho e a ocorrência de ansiedade e de depressão, averiguando se houve desencadeamento de transtornos somáticos e/ou transtornos nas relações sociais dos indivíduos. Em todos os casos estudados, constatamos que houve aumento significativo de sintomas após o afastamento e que o retorno ao trabalho foi impossibilitado devido à persistência da patologia e ao desenvolvimento de outras manifestações. Assim, o afastamento pôde ser considerado um estímulo estressor, pois além de causar transtornos psíquicos provocou alterações orgânicas.
Keywords: Work accident; Anxiety and depression; Acidente de trabalho; Ansiedade e depressão